When Freedom of Expression Goes Awry on Social Media: An Analysis of Comments on Naij.Com in the Run-Up to the 2015 Presidential Elections in Nigeria (Global Journal of Human-Social Science, 2018)
This paper carefully analyzed public comments on Naij.com facebook page with the goal to expose the direction in which the comments of social media users followed in their bid to show support and canvass votes for their preferred candidates in the run-up to the 2015 presidential elections. Although the traditional media were perceived to have carried more venom in their campaign advertisements and commentaries, this study focused on whether or not social media users abused their freedom of expression on the facebook platform, and whether tribal sentiment determined the direction of comments. The findings revealed that facebook users posted abusive comments on Naij.com news page, but posted more comments endorsing candidates of their choice, followed by comments rejecting candidates they did not want. Tribal sentiment clearly reflected in the direction of comments, which finally played out in the outcome of the presidential election results.
Keywords: direction of comments; freedom of expression; social media; democracy; electioneering campaign